The Effect of the Pair Check Cooperative Learning Model Assisted by Wordwall on the Mathematics Learning Outcomes - Tiya Meita Dor Opat Purba; Regina Sipayung; Eka Margareta Sinaga; Darinda Sofia Tanjung; Frikson Purba (International Journal of Research in Education, 2026)
Mathematics is a fundamental subject in elementary education because it develops students' logical reasoning, problem-solving skills, and conceptual understanding. However, many elementary students continue to experience difficulties in learning mathematics due to teacher-centered instructional practices, limited student interaction, and insufficient use of innovative learning media. These conditions often result in low learning outcomes, particularly in understanding the concepts of the area and perimeter of plane figures. Therefore, effective instructional strategies that promote active learning and meaningful student engagement are needed. This study aimed to examine the effect of the Pair Check Cooperative Learning Model assisted by Wordwall media on the mathematics learning outcomes of Grade V students at UPT SD Negeri 018 Aeklung, Humbang Hasundutan Regency, during the 2025/2026 academic year. This research employed a quantitative approach using a pre-experimental one-group pre-test–post-test design. The participants consisted of 27 Grade V students selected through total sampling. Data were collected using mathematics achievement tests and a student response questionnaire. The collected data were analyzed using descriptive statistics, normality testing, Pearson Product–Moment correlation, coefficient of determination, and t-test analysis. The findings revealed that students' mean score increased from 61.30 on the pre-test to 73.63 on the post-test, indicating improved mathematics achievement after the intervention. Statistical analyses also demonstrated a significant positive effect of the Pair Check Cooperative Learning Model assisted by Wordwall media on students' mathematics learning outcomes. The study concludes that integrating cooperative learning with interactive digital media creates an engaging learning environment that enhances conceptual understanding, active participation, collaboration, and mathematics achievement among elementary school students.